Anti-diabetic effects of Lepidium meyenii (maca) and marine collagen peptide (MCP) in Blackbelt® coffee on type II diabetes mellitus rat model - Othman, Najwa Hanim; Ismawi, Hidayatul Radziah; Mohd Zainudin, Maizura; Abd Fuaat, Azliana (Faculty of Medicine, UKM, 2023)
Introduction: The potential use of Lepidium meyenii (maca) and marine collagen peptide (MCP) for the treatment of type 2 diabetes mellitus (T2DM) symptoms has piqued researchers’ curiosity. However, no research has been conducted to investigate how the combination of these two components may benefit in the treatment of T2DM. The study sought to investigate the potential beneficial effects of combining maca and MCP in Blackbelt® on insulin and blood glucose levels in T2DM rats. Materials and Methods: 36 male Sprague Dawley rats with T2DM induced by high-fat diet/streptozocin (40 mg/kg) were used. Metformin (200 mg/ kg), maca (13 mg/kg), MCP (264 mg/kg), maca/MCP® (Blackbelt® formulation), and Blackbelt® (132 g/kg) were administered orally to rats for 28 days. Fasting blood glucose (FBG) and serum insulin levels were monitored periodically. Results: The FBG levels in every group decreased from week 0 to week 4. However, results revealed that only oral administration of metformin, maca, MCP and Blackbelt® can significantly decrease the FBG levels in T2DM rats (p <0.05). Among them, oral administration of metformin showed the lowest FBG levels at week 4 followed by MCP, Blackbelt®, maca, maca/MCP® (Blackbelt® formulation) and diabetic control group. The findings demonstrated that by week 4, rats given maca, MCP, and Blackbelt® had increased insulin secretion. When compared to the control group, only rats treated with MCP and Blackbelt® exhibited substantial increases in insulin secretion (p <0.05). Conclusion: Even though maca/MCP® formulation did not have significant anti-diabetic effects, Blackbelt’s® was still capable of lowering blood sugar and increasing the secretion of insulin against high-fat diet/streptozocin- induced diabetes. Blackbelt’s® anti-diabetic effect was comparable but not better than metformin.